2019
DOI: 10.1016/j.physletb.2019.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Probing the CP-Violation effects in the hττ coupling at the LHC

Abstract: A new method used to calculate the neutrino for all major tau hadronic decay event by event at the LHC is presented. It is possible because nowadays better detector description is available. With the neutrino fully reconstructed, matrix element for each event can be calculated, the mass of the Higgs particle can also be calculated event by event with high precision. Based on these, the prospect of measuring the Higgs CP mixing angle with h → ττ decays at the LHC is analyzed. It is predicted that, with a detail… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…The previous studies of the collider measurements of the CPV in the Higgs Yukawa couplings can be found in refs. [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99].…”
Section: A3 the Yukawa Couplings In The Cpv 2hdmmentioning
confidence: 99%
“…The previous studies of the collider measurements of the CPV in the Higgs Yukawa couplings can be found in refs. [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99].…”
Section: A3 the Yukawa Couplings In The Cpv 2hdmmentioning
confidence: 99%
“…6 Similar χ 2 Imp expressions for tracks whose trajectories do not intersect with the tau flight direction (due to resolution effects) can be found in [33,34] 7 They are tuned such that the fraction of events with good reconstructed neutrinos is the largest, and they also control the relative weight of Eq. In the per-event minimization of Eq.…”
Section: Reconstruction Of the Neutrinosmentioning
confidence: 84%
“…While the spin correlation can be partially obtained with only visible decay products [31,32], the information of neutrinos is important to help improve the reconstruction of the tau spin correlation. The technique to reconstruct the neutrino momenta from tau decays developed in our previous works [33,34] is used for the low energy e − e + collisions which makes use of the full information per event including the impact parameters of charged tracks from tau decays. Because Belle-II started taking data with the full detector in 2019 [35], it is worthwhile to simulate data with the Belle-II detector, and investigate the sensitivity one can expect from it for both tau EDM and g-2 searches.…”
Section: Event Selection and Reconstruction Of Neutrinos From τ Decaymentioning
confidence: 99%
See 1 more Smart Citation
“…In the future it will be important to further improve the sensitivity to a possible CPodd component of this coupling at the LHC and future colliders, and to evaluate the baryon asymmetry corresponding to the constrained amount of CP -violation. An experimental HL-LHC projection [37] and several phenomenological analyses [38][39][40][41] have already been performed in this direction. Machine Learning (ML) may also play a useful role in further scrutinizing the CP nature of the Higgs-τ interaction [42,43].…”
Section: Jhep05(2020)056mentioning
confidence: 99%